2016
DOI: 10.3109/0284186x.2015.1115123
|View full text |Cite
|
Sign up to set email alerts
|

Trends in tumors in the central nervous system in elderly in Denmark, 2008–2012

Abstract: Background Tumors in the central nervous system (CNS) comprise a heterogeneous group of tumors with different treatment strategies and prognoses. Current treatment regimens are based on studies on patients mainly younger than 70 years. The aim of the present study was to analyze and describe trends in incidence, mortality, prevalence, and relative survival in Denmark from 1980 to 2012 focusing on patients older than 70 years. Material and methods Tumors in the CNS were defined as ICD-10 codes C70-72, D32-33 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…This is in agreement with previous publications that recommended an in-depth analysis for age, gender-specific mortality rates [17] and other factors that affecting the pattern of mortality [16]. In another publication the mortality rates related to the tumors of central nervous system reported to be increased within all age groups, most significantly in patients aged 70 years or older [18]. Death reported due to multiple sclerosis in this study occurred at the age between 22 and 66 years old.…”
Section: Disscussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous publications that recommended an in-depth analysis for age, gender-specific mortality rates [17] and other factors that affecting the pattern of mortality [16]. In another publication the mortality rates related to the tumors of central nervous system reported to be increased within all age groups, most significantly in patients aged 70 years or older [18]. Death reported due to multiple sclerosis in this study occurred at the age between 22 and 66 years old.…”
Section: Disscussionsupporting
confidence: 92%
“…In this study there were 19 death reports due to secondary malignant neoplasm of brain. Previous publication suggested that due to dissimilar presentation of tumor in the central nervous system, it needs dissimilar management approaches [18]. Danilova et al, in 2016 confirmed that for public health analysis data related to death should be comparable on system of producing information on cause of death across regions and/ or over time [2].…”
Section: Disscussionmentioning
confidence: 99%
“… 16 In terms of absolute number of people affected by neurological disorders, most of the increase in the burden was associated with ageing of the population and population growth. 9 Increasing incidence of stroke in low-income and middle-income countries, 17 increasing prevalence of multiple sclerosis, 18 , 19 increasing incidence of epilepsy in elderly people, 20 increasing prevalence of tension-type headache, 21 and increasing incidence of brain tumours in elderly people 22 have been reported elsewhere. Findings from other studies have reported that it is difficult to assess trends in prevalence and incidence of Parkinson's disease because of changes in case definitions over time.…”
Section: Discussionmentioning
confidence: 99%
“…There was a large rise in the absolute numbers of prevalent cases of Alzheimer's disease and other dementias ( 44 , 45 ). In addition, an increasing incidence of stroke ( 46 ), epilepsy ( 47 ), and intracranial malignancies in elderly people ( 48 ), as well as growing prevalence of multiple sclerosis ( 49 , 50 ) have been reported in different regions. The increasing burden of these neurological conditions, found to be an established risk factor for BP, may account for part of the rising incidence of BP.…”
Section: Putative Explanations For This Surgementioning
confidence: 99%